MOLECULAR DOCKING STUDY, SYNTHESIS AND INVITRO EVALUATION OF ANTITUMOR ACTIVITY OF NOVEL NAPHTHYLIDENE BASE OF BENZOIC ACID DERIVATIVES: Life Sciences-Bioinformatics - J.NELSON SAMUEL JEBASTIN; T. RAMESH KUMAR; D.EVANGELIN (International Journal of Life Science and Pharma Research, 2022)
Cancer therapies targeted developing cell cycle-based mechanism that emulates the body’s natural process in order to stop the growth of cancer cells. This approach can limit the damage to normal cells and the accompanying side effects caused by conventional chemotherapeutic agents. Inhibition of histone deacetylase (HDAC) enzymes is emerging as an innovative and effective approach for the treatment of cancer. Nineteen compounds of the naphthylidene base of benzoic acid derivatives were designed and tested in silico for their interaction with histone deacetylase (HDAC8) enzyme. 19 ligands docked with Histone deacetylase 8 Human HDAC8 (PDB ID: 1T69) using Glide program (Version 5.0, Schrodinger, LLC, New York, 2008) and designed, synthesized and evaluated for their ability to inhibit cell proliferation in cancer cell lines. Based on the docking score 4-((2-hydroxynaphthalen-1-yl)methyleneamino) benzoic acid showed highest docking score of -5.8214, which is important for HDAC8 inhibition. In this present investigation, molecular docking, design, synthesize and evaluated for in vitro antitumor activity to identify novel active compound targeting the HDAC8 protein. Among the 19 compounds A19 showed promising activity against human cervical cancer cell line.